2022
DOI: 10.3390/cells11040621
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Effects of PPAR Ligands in Glioblastoma

Abstract: Glioblastoma (GB), also known as grade IV astrocytoma, represents the most aggressive form of brain tumor, characterized by extraordinary heterogeneity and high invasiveness and mortality. Thus, a great deal of interest is currently being directed to investigate a new therapeutic strategy and in recent years, the research has focused its attention on the evaluation of the anticancer effects of some drugs already in use for other diseases. This is the case of peroxisome proliferator-activated receptors (PPARs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 84 publications
0
12
0
6
Order By: Relevance
“…Oxylipins are considered as ligands for PPARs ( Cowart et al, 2002 ; Flores et al, 2005 ; Liu et al, 2005 ; Oh et al, 2009 ; Korbecki et al, 2019 ; Basilotta et al, 2022 ) and, thus, it was hypothesized that elevated concentrations of distinct lipoxins observed after knock-out of tafazzin contribute to TAZ-dependent changes in gene expression in C6 cells. Therefore, C6 cells were exposed to 8,9 EET, which showed the greatest increase in concentration under tafazzin knock-out in C6 TAZ cells, at 3 µM concentration for 24 h and then expression of selected genes was determined by RT-qPCR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxylipins are considered as ligands for PPARs ( Cowart et al, 2002 ; Flores et al, 2005 ; Liu et al, 2005 ; Oh et al, 2009 ; Korbecki et al, 2019 ; Basilotta et al, 2022 ) and, thus, it was hypothesized that elevated concentrations of distinct lipoxins observed after knock-out of tafazzin contribute to TAZ-dependent changes in gene expression in C6 cells. Therefore, C6 cells were exposed to 8,9 EET, which showed the greatest increase in concentration under tafazzin knock-out in C6 TAZ cells, at 3 µM concentration for 24 h and then expression of selected genes was determined by RT-qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…Oxylipins, including HETEs and EETs, have been described as endogenous ligands of PPARs ( Cowart et al, 2002 ; Flores et al, 2005 ; Liu et al, 2005 ; Oh et al, 2009 ; Korbecki et al, 2019 ; Basilotta et al, 2022 ). Furthermore, 12 out of the 12 genes that were differentially expressed in C6 TAZ cells as confirmed by RT-qPCR (shown in Figure 2 ), according to the eukaryotic promoter database (EPD) ( Dreos et al, 2013 ) contained at least one putative PPARG or PPARA: RXRA binding site in their promoters (Online Supplementary Table S2 ; p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…PPAR-γ is frequently expressed in various cancer cells, including breast, lung, colon, lips, kidney, pancreatic and thyroid [ 32 ]. Several studies have revealed that PPAR-γ activation by its agonists imposes cell cycle arrest [ 33 ], apoptosis [ 34 ], angiogenesis [ 35 ], inhibition [ 36 ], and redifferentiation [ 37 ], which are the key molecular processes associated with the prevention of tumor growth and progression. The expression of angiogenesis-related proteins such as vascular endothelial growth factor (VEGF) and cyclooxygenase-2 as well as inflammatory mediators in the tumor microenvironment are all inhibited by PPAR-γ activation [ 38 ].…”
Section: Functional Diversity Of Ppar-γmentioning
confidence: 99%
“…Numerous studies illustrated that 15d-PGJ2 may serve as an anti-cancer agent in oral squamous cell carcinoma cells [ 106 ] and gastric cancer [ 107 ] by promoting cell apoptosis. In addition, the protein receptor has been readily reported to induce apoptosis and inhibited proliferation of numerous other tumor cells [ 36 , 108 , 109 ]. Recently, a study illustrated chemopreventive nature of pioglitazone in a pre-clinical mouse model of squamous lung carcinoma.…”
Section: Ppar-γ Agonists In Various Diseasesmentioning
confidence: 99%
“…The DNA sequence in the promoter region of genes, called the peroxisome proliferator response element (PPRE), is recognized by DBD. On the other hand, a ligand-binding domain (LBD) in the C-terminus is responsible for the specificity of the ligand and dimerization of the receptor with the retinoid X receptors (RXR) [ 84 ]. PPARs translocate to the nucleus after interacting with specific ligands (synthetic or non-synthetic) [ 85 ].…”
Section: Peroxisome Proliferator-activated Receptorsmentioning
confidence: 99%